`lim_(x->oo) sqrt(x+1) + sqrt(x-1) `

`==> lim_(x->oo) (sqrt(x+1)+sqrt(x-1))X (sqrt(x+1)-sqrt(x-1))/(sqrt(x+1)-sqrt(x-1))`

`==> lim_(x->oo) ((x+1) - sqrt(x^2-1) +sqrt(x^2-1) - (x-1))/(sqrt(x+1)-sqrt(x-1))`

`==> lim_(x->oo) (x+1-x+1)/(sqrt(x+1)-sqrt(x-1))`

`==> lim_(x->oo) 2/(sqrt(x+1)-sqrt(x-1)) = 2/oo = 0`

`==>lim_(x->oo) sqrt(x+1) + sqrt(x-1) = 0`

``

Multiply squareroot(x+1)+squareroot(x-1) by the conjugate squareroot(x+1)-squareroot(x-1) and you'll get a difference of squares.

[squareroot(x+1)+squareroot(x-1)][squareroot(x+1)-squareroot(x-1)]=[squareroot(x+1)]^2-[squareroot(x-1)]^2

[squareroot(x+1)+squareroot(x-1)][squareroot(x+1)-squareroot(x-1)]=x+1-x+1

[squareroot(x+1)+squareroot(x-1)][squareroot(x+1)+squareroot(x-1)]=2

limit [squareroot(x+1)+squareroot(x-1)]=limit [2/(squareroot(x+1)-squareroot(x-1))] = 2/infinite = 0

**Answer: The limit of the addition is 0 if x approaches to
infinite.**

## See eNotes Ad-Free

Start your **48-hour free trial** to get access to more than 30,000 additional guides and more than 350,000 Homework Help questions answered by our experts.

Already a member? Log in here.